Fundamental Principles And Therapeutic Significance Of Rasashastra In Ayurvedic Pharmaceutics: A Review - Kumar, Ajit; Dwivedi, Prabhat Kumar (Journal of Neonatal Surgery, 2025)
Rasashastra, a specialized branch of Ayurveda, focuses on the alchemical processing and therapeutic utilization of metals, minerals, and herbo-mineral compounds. Rooted in classical Ayurvedic pharmaceutics, it aims to transform potentially toxic substances into safe, bioavailable, and highly potent medicines through systematic procedures such as Shodhana (purification), Marana (calcination/incineration), and Samskara (processing). These techniques enhance therapeutic efficacy while minimizing adverse effects, ensuring that the end products—particularly Bhasma, Rasaushadhi, Pottali, and Kupipakwa preparations—are suitable for clinical use in various chronic and refractory diseases.This review article explores the fundamental principles, traditional formulations, and the unique pharmaceutical techniques employed in Rasashastra. It also analyzes the therapeutic significance and clinical applications of these formulations in the light of modern pharmacology. With a growing demand for evidence-based traditional medicines, the integration of Rasashastra into modern health systems calls for scientific validation, pharmacovigilance, and standardized protocols.Furthermore, the review emphasizes the relevance of Rasashastra in drug discovery, nanomedicine, and bio-enhanced delivery systems. By aligning classical Ayurvedic wisdom with current scientific methodologies, Rasashastra holds great promise for contributing to global healthcare. The article advocates for interdisciplinary research, practitioner training, and regulatory frameworks to ensure the safe and effective use of Rasashastra-based therapeutics in the modern era.